Computer aided engineering for the design of flight control and hydraulic systems - Dieter Scholz (SAE technical papers, 1996)
A Computer Aided Engineering (CAE) tool has been developed for the design of flight control and hydraulic systems. The CAE tool consists of independent modules that build on each others results. For the programing of each of these modules it was necessary to thoroughly review the state-of-the-art. This paper presents a structured design procedure for hydraulic systems of transport category aircraft aiming at maximum performance at minimum weight (and cost). Reference is made to CAE modules written to support a substantial part of this design procedure. The module for the steady state calculation of hydraulic systems is further detailed. © Copyright 1996 Society of Automotive Engineers, Inc.